Spyware and Adware - Aycock, John.; SpringerLink (Online service) (Boston, MA : Springer US, 2011)
Spyware and Adware introduces detailed, organized, technical information exclusively on spyware and adware, including defensive techniques. This book not only brings together current sources of information on spyware and adware but also looks at the future direction of this field. Spyware and Adware is a reference book designed for researchers and professors in computer science, as well as a secondary text for advanced-level students. This book is also suitable for practitioners in industry.
Preface -- Introduction -- Getting There -- Staying There -- Keylogging -- Phoning Home -- Advertising -- Advertisement Implementation -- Tracking Users -- Conclusion -- References -- Index.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Data protection; Data structures (Computer science).; Data encryption (Computer science).; Information systems; Computer Science; Systems and Data Security; Computer Communication Networks; Data Encryption; Information Systems Applications (incl.Internet).; Computer Systems Organization and Communication Networks; Data Structures, Cryptology and Information Theory